The Effect of Corn Replacement by Sorghum in Broiler Diets on the Internal Organ - Vebriani, Koleta; Mulyantini Sekar Sari, Ni Gusti Ayu; Theedens, Jonas Fritz; Suryatni, Ni Putu Febri (JURNAL ILMIAH PETERNAKAN TERPADU, 2025)
This research aims to investigate the effect of corn replacement by sorghum in broiler diets on the internal organ. The method used was a Completely Randomized Design with 4 treatments and 5 replications, and in each replicate, there was 5 chickens. The treatments given were P0: 0% sorghum in the ration (100% corn as control), P1: 25% corn replacement with sorghum, P2: 50% corn replacement with sorghum, P3: 75% corn replacement with sorghum. The variables measured were liver weight, gizzard weight, small intestine weight and small intestine length. The data was analyzed using Analysis of Variance (ANOVA) and if there was a significant effect, Duncan's further test would be continued to see the differences in each treatment sample. Statistical analysis show that replacing 75% of corn with sorghum in diet had no significant effect (P>0.05) on liver and gizzard weight, and 50% replacement of corn with sorghum had a significant effect on small intestine weight and small intestinal length. In conclusion, 75% corn replacement with sorghum did not have negative effect on liver and gizzard weight, whereas 50% corn replacement with sorghum decreased small intestinal weight and small intestinal length.